PROBLEMATIKA HUKUM PEMBAGIAN WARIS 2:1 DALAM PENDEKATAN TEORI QATH’I ZHANNI - Al Robin (Fakultas Syariah IAI Muhammadiyah Bima, 2018)
In inheritance law of Islam, the Qur’an has idealized and specified clearly that sons inherit twice that of daughters. Instead of legal practice some communities in Indonesia that the sons received the same parts with the daughters. Even dividing when the heir is still alive because their lack of understanding of the text qath’i zhani. Qath’i al-dalalah Islamic inheritance texts about the distribution of 2: 1 between sons and daughters, according to the ulama not absolutely necessary, as the opinion of Munawir Sjadazali. Thus it was stated by Mashdar Farid Mas'udin, that the qath’i was only the principles of justice are conceived by the verses of the Islamic inheritance and not the provisions of section men who got twice that of women. But this kind of division has implications for the strength of law, if there is a dispute in the future then it is incapable to be accountable because distribution is outside of the provisions of the Qur'an and Law and also, this sort of thing would have implications for the impartial justice in Islamic inheritance law of the balance between the rights of the estate obtained by the obligations or burdens that must be borne or fulfilled among the heirs. Therefore, the sense of justice in Islamic inheritance law is not measured by the similarity degree between the heirs, but is determined based on the large-small burden or responsibility entrusted to them, in terms of generality state/human life.